Studie skladového hospodářství ve výrobním podniku - Kulíková, Alena (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Diplomová práce se věnuje řízení procesu skladování ve firmě Gmont cable, s.r.o., která se zabývá výrobou kabelových svazků pro automotive a průmyslové stroje. Dokument popisuje proces skladování, analyzuje současný stav řízení zásob v podniku a zamýšlí se nad vhodným řešení tohoto procesu. Cílem práce je zefektivnění procesu skladování a hledání zdroje úspor nákladů.

The master´s thesis is concerned with the process of storage in Gmont cable, s.r.o., the company interested in cable harnesses for the automotive and industrial machines. The document describes and analyses the existing situation of the process of storage and also reflects on the suitable concept of its solving. The purpose is the effectiveness of the process and searching for the savings source of costs.
The Study of Storage in Manufacturing Corporation
Keywords: Skladování; řízení zásob; materiál; proces; logistika.; Storage; Management of Supplies; Material; Process; Logistics.